How to Precisely Open the Internal Auditory Canal for Resection of Vestibular Schwannoma via the Retrosigmoid Approach - Jia, Chenguang; Xu, Chengshi; Wang, Mengyang; Chen, Jincao (Frontiers in Surgery, 2022)
Objective: The aim of this study was to investigate how to precisely expose the intrameatal portion of vestibular schwannomas (VSs) without damaging the labyrinth. Methods: This was a retrospective study of patients who had undergone retrosigmoid resection of a VS in our institution from April 2018 to December 2021. The patients were divided into microsurgery (MS) and navigation endoscopic-assisted (combined surgery, CS) groups and the effects of image guidance and endoscopy evaluated. The tumors in the CS group were then divided into medial and lateral types by fusion imaging and the differences between the two types analyzed. Results: Data of 84 patients were analyzed. Residual tumor was detected by postoperative MRI at the fundus of the internal auditory canal in 5 of the 31 patients in the MS group and 1 of the 53 in the CS group. The labyrinth was damaged in four patients in the MS group but was not damaged in any of the CS group patients. The CS group included 29 lateral type and 24 medial type schwannomas. Endoscopic-assisted resection of residual tumor in the IAC was performed significantly more often on medial than on lateral tumors. Conclusion: Navigation and endoscopy are useful in assisting the exposure of the intrameatal portion of VSs. Preoperative MRI/CT fusion imaging is helpful in preoperative evaluation and surgical planning in patients undergoing VS surgery. Tumors of the medial type require endoscopic assistance for resection.